Comparative analysis of key performance indicators in Euroleague and national - Plakias, S.; Kokkotis, C.; Pantazis, D.; Tsatalas, T. (Journal of Physical Education and Sport, 2024)
Background: Understanding the performance metrics that underpin team success in the dynamic world of professional basketball is crucial. This study originated from the increasing academic and professional interest in performance analytics, focusing on how teams in elite leagues, such as the Euroleague and their respective national leagues, adapt and perform based on specific key performance indicators (KPIs).